Advancing Behavioral HIV Prevention: Adapting an Evidence-Based Intervention for People Living with HIV and Alcohol Use Disorders - M. L. Armstrong; A. M. LaPlante; F. L. Altice; M. Copenhaver; P. E. Molina (AIDS Research and Treatment)
Alcohol use disorders (AUDs) are highly prevalent among people living with HIV/AIDS (PLWHA) and are associated with increased HIV risk behaviors, suboptimal treatment adherence, and greater risk for disease progression. We used the ADAPT-ITT strategy to adapt an evidence-based intervention (EBI), the Holistic Health Recovery Program (HHRP+), that focuses on secondary HIV prevention and antiretroviral therapy (ART) adherence and apply it to PLWHA with problematic drinking. Focus groups (FGs) were conducted with PLWHA who consume alcohol and with treatment providers at the largest HIV primary care clinic in New Orleans, LA. Overall themes that emerged from the FGs included the following: (1) negative mood states contribute to heavy alcohol consumption in PLWHA; (2) high levels of psychosocial stress, paired with few adaptive coping strategies, perpetuate the use of harmful alcohol consumption in PLWHA; (3) local cultural norms are related to the permissiveness and pervasiveness of drinking and contribute to heavy alcohol use; (4) healthcare providers unanimously stated that outpatient options for AUD intervention are scarce, (5) misperceptions about the relationships between alcohol and HIV are common; (6) PLWHA are interested in learning about alcohol’s impact on ART and HIV disease progression. These data were used to design the adapted EBI.